BIOLOGICAL AND PSYCHIC AGING: NARRATIVE LITERATURE REVIEW - Baroni Araujo, Gustavo; Gomes dos Santos, Jordane; Guerra Drummond Júnior, Délio; Ellem Silva de Souza, Lizandra; Emanuelly Leal Araújo, Yasmin; Cesar Pereira da Silva, Júlio; Henrique de Sousa Figueiredo, Iaggo; Wágner Holanda Lima, Mariel; Maria dos Santos da Silva Apolinário, Joelma; Noleto Leao, Rafael; de Carvalho Alves, Winícius; Fernandes de Carvalho Farias, Anderson (Journal of Interdisciplinary Debates, 2022)
Biological aging is relentless, active and irreversible, causing greater vulnerabilities to the body to external and internal aggressions. The objective of this work is to discuss general aspects that occur with aging, as well as the main causes of biological and psychological aging based on the scientific literature. This is a bibliographic review of the narrative literature review method, carried out from March 2022 to May 2022. The guiding question was: “What is the most relevant information about biological and psychological aging in the elderly?” The searches were carried out through the SciELO database (Scientific Electronic Library Online), Google Scholar and the Virtual Health Library (BVS). The descriptors/keywords used were: “Biological aging” and “Psychic aging” combined with the Boolean operator “AND” in the period from 2018 to 2021. Inclusion criteria were original and review studies made available in full in Portuguese. In total, 6 articles made up this study. The various factors of human aging are observed, and they point to losses, changes in sexual functionality, physical changes, in addition, the signs of functional aging appear discreetly throughout life, being called senescence. Biological and psychic aging occurs in different ways in each individual. The approach to aging must be multifaceted, as the quality of life of the elderly population can be positively and negatively affected by a wide range of factors